Kształtowanie pamięci o masowych represjach w rosyjskim internecie - Kadykało, Anna (Przegląd Rusycystyczny, 2016)
Формирование памяти о массовых репрессиях в российском интернет-пространстве Среди многих видов интернет-активности молодые россияне обсуждают вопро-сы, касающиеся сталинских репрессий. отношение пользователей интернета к этим трагическим событиям проявляется, например, в интернет-дискуссиях и посредством создания демотиваторов. Эти носители памяти могут рассматри-ваться в качестве артефактов «постпамяти», свойственной, главным образом, молодому поколению, которое не имеет трагических воспоминаний, связанных с репрессиями. Формирование памяти массовых репрессий является частью более масштабного процесса формирования культурной памяти россиян, основанной на трактовке советского прошлого. Ссылаясь на проявления «постпамяти», молодые россияне могут лучше понять историю своей страны и найти указания в окружающей их действительности. Shaping the memory of the mass repressions in Russian Internet Among the many types of Internet activity young Russians discuss the issues of the mass repressions of the Stalin era. The attitude of Internet users to these tragic events is expressed not only in many online discussions, popular social networking sites, but also through the creation of (very popular now) demotivators. These carriers of memo-ry can be considered as the artifacts of “post-memory”, which is characterized mainly for young generation of Russians who do not have experienced the traumatic memories connected with mass repressions. Constructing the memory of the mass repression is a part of a broader process of constructing the cultural memory of Russians based on the interpretation of the Soviet past. By referring to the manifestations of “post-memo-ry”, young Russians can better understand the difficult history of their country and find landmarks in the surrounding reality.